2017
DOI: 10.1002/pssb.201700213
|View full text |Cite
|
Sign up to set email alerts
|

Unfolding phonon spectra by smearing of vibrational eigenmodes

Abstract: A method to unfold phonon band structure is proposed which is as simple and general as those used in the electronic structure calculations. It is achieved using continuous Bloch representation of vibrational eigenmodes. The results of lattice dynamics calculations for perfect and defect diamond as well as for calcium fluorite demonstrate good accuracy and performance of the approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…In alloys or defective systems, where the translational symmetry is broken, the unfolding/projection procedure still works, but leads to each SC mode having contributions from q-points throughout the PC BZ with different weights. This type of unfolding procedures have already been used in the past to analyze both the electronic and phonon band structures of alloys [44][45][46][47]. Baroni et al found that the GDOS of the primitive cell can be used to closely approximate the Raman spectra [42] in alloys.…”
Section: A Theoretical Frameworkmentioning
confidence: 99%
“…In alloys or defective systems, where the translational symmetry is broken, the unfolding/projection procedure still works, but leads to each SC mode having contributions from q-points throughout the PC BZ with different weights. This type of unfolding procedures have already been used in the past to analyze both the electronic and phonon band structures of alloys [44][45][46][47]. Baroni et al found that the GDOS of the primitive cell can be used to closely approximate the Raman spectra [42] in alloys.…”
Section: A Theoretical Frameworkmentioning
confidence: 99%